2017
DOI: 10.2748/tmj/1498269625
|View full text |Cite
|
Sign up to set email alerts
|

Non-hyperbolic unbounded Reinhardt domains: non-compact automorphism group, Cartan's linearity theorem and explicit Bergman kernel

Abstract: In the study of the holomorphic automorphism groups, many researches have been carried out inside the category of bounded or hyperbolic domains. On the contrary to these cases, for unbounded non-hyperbolic cases, only a few results are known about the structure of the holomorphic automorphism groups. Main result of the present paper gives a class of unbounded non-hyperbolic Reinhardt domains with non-compact automorphism groups, Cartan's linearity theorem and explicit Bergman kernels. Moreover, a reformulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…Our next task is to show that f : D p → D q is linear, that is, f is a non-singular linear transformation of C N such that f (D p ) = D q . This can be shown along the same lines as in the proof of Yamamori [25,Theorem 4.1]. Indeed, the inclusion M ⊂ A 2 (D) in (2.2) guarantees that K D s (0, 0) > 0 and T D s (0, 0) is positive definite for s = p, q, where K D s is the Bergman kernel for D s and T D s is an N × N matrix defined by…”
Section: Proof Of Theoremsupporting
confidence: 53%
See 2 more Smart Citations
“…Our next task is to show that f : D p → D q is linear, that is, f is a non-singular linear transformation of C N such that f (D p ) = D q . This can be shown along the same lines as in the proof of Yamamori [25,Theorem 4.1]. Indeed, the inclusion M ⊂ A 2 (D) in (2.2) guarantees that K D s (0, 0) > 0 and T D s (0, 0) is positive definite for s = p, q, where K D s is the Bergman kernel for D s and T D s is an N × N matrix defined by…”
Section: Proof Of Theoremsupporting
confidence: 53%
“…This together with f ( D p ) = D q from Theorem 1 yields that f (0) = 0. Thus, by the same method as in the proof of Yamamori[25, Theorem 4.1] based on the results in Ishi and Kai [7, Propositions 2.1 and 2.6] it can be shown that f is linear, as desired. Finally, express f (z, w) = (Az, Bw) by some A ∈ GL(n; C) and B ∈ GL(m; C).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…, θ n ∈ R. For Reinhardt domains, the following theorem is known. This theorem follows from Proposition 3.2 after checking that K D (0, 0) > 0 and that T D (0, 0) is positive definite as in [28].…”
Section: Cartan's Theoremmentioning
confidence: 88%
“…For works related to the Hua domain, see [17], [23]. In [28], the Bergman kernel and the automorphism group of Ω m,p are studied when Ω = C n and Φ(z) = e −µ z 2 . Let us consider the domain…”
Section: Introductionmentioning
confidence: 99%